EVALUASI KEBIJAKAN DISIPLIN PEGAWAI NEGERI SIPIL (Studi Pelaksanaan Peraturan Pemerintah Nomor 53 Tahun 2010 tentang Disiplin Pegawai Negeri Sipil Pada Badan Kesatuan Bangsa, Politik dan Masyarakat Kabupaten Kutai Kartanegara) - Efri novianto (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2015)
This research aimed to evaluate and know the factors supporting and restricting Government Regulation No. 53 in 2010 to Discipline Civil Servants at the Badan Kesbangpolmas in Kutai Kartanegara Regency. This type of research is qualitative deskriftif. Techniques used in determining the source of data is a Purposive Sampling method Snowballing Sampling. Data analysis techniques are used to use the interactive model.Based on the results of the study can be concluded that the results are as set forth in desired Government Regulation No. 53 in 2010 about the Discipline of Civil Servants at the Badan Kesbangpolmas in Kutai Kartanegara Regency has been reached but has yet to maximum. Efforts are being made to achieve the desired results have been quite a lot of that through socialization activities and sending personnel to follow bimtek Government Regulation No. 53 in 2010 about the Discipline of Civil Servants. Results achieved from the implementation of Government Regulation No. 53 in 2010 was pretty successful in resolving the problems of the discipline of Civil Servants at the Badan Kesbangpolmas in Kutai Kartanegara Regency, but not a maximum. Benefits from the implementation of Government Regulation No. 53 in 2010 is the growing discipline of Civil Servants on the Badan Kesbangpolmas in Kutai Kartanegara Regency. The added benefit of increased discipline of Civil Servants increased the performance of Civil Servants to do with achievement of the objectives of the Organization, whereas for the community is the increased public services provided. The response of Civil Servants against the presence of Government Regulation No. 53 in 2010 is quite good, it is characterized by the growing Discipline of Civil Servants. Results on disposal useful for Civil Servants to improve discipline. For the Government, an increase of discipline will be directly proportional to improved performance, and improved performance will be directly proportional to the increase in the public service. Factors that support the Government Regulation No. 53 in 2010 is due to the rules or sanctions and firmness due to Kutai Kartanegara Regent policy about granting of incentives or allowances for additional earnings and the giving of money to eat that accumulated from the attendance rates of Civil Servants. While the factors that hamper the Government Regulation No. 53 in 2010 is specifically due to lack of leadership in applying sanctions for Civil Servants who violate discipline, low awareness of Civil Servants to obey the rules that existed in the Government Regulation No. 53 in 2010 and lack of socialization related rules regarding the discipline of Civil Servants as Government Regulation No. 53 in 2010. Keywords: Evaluation, Discipline, Civil Servant